Revenge and reconciliation understanding South Asian history - Gandhi Rajmohan (New Delhi Penguin Books, 1999)
In this study the author underscoring the prominence in the Mahabharata of the revenge impulse, follows its trajectory in South Asian history. Side by side he traces the role played by reconcilers up to present times like Buddha, Mahavira and Asoka.Encom
Keywords: South Asia-history